PENGARUH PERBEDAAN INTENSITAS CAHAYA MATAHARI TERHADAP PANJANG HIPOKOTIL KOPI ROBUSTA (Coffea robusta. L) - Ismoyojati, Roni; Ratnasari, Ika Fitriana Dyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
The intensity of sunlight is an environmental factor that plays a very important role as a key to success in cultivating plants, especially robusta coffee plants. During the growth and development period, coffee, which is a C3 plant, does not really need maximum sunlight intensity, but it is necessary to know the optimum light intensity to get the best hypocotyl length growth. This research was conducted in the experimental field of Lamandau Polytechnic from March to May 2024. The field experiment was arranged using a Randomized Block Design (RBD) with 5 treatments, each treatment was N0 = Treatment without using Paranet as a shade; N1 = Treatment using 1 layer of paranet; N2 = Treatment using 2 layers of paranet; N3 = Treatment using 3 layers of paranet; N4 = Treatment using 4 layers of paranet. Observations were made by observing the intensity of sunlight, the time of emergence of seedlings, germination power and hypocotyl length. Data analysis using ANOVA and if there is a significant difference, it will be continued using the 5% DMRT test. Regression analysis was used to determine the relationship between sunlight intensity and coffee hypocotyl length. The results of the study showed that shade treatment using 3 layers of paranet (N3) and 4 layers (N4) with an average light intensity below 30% was able to optimally increase the length of the hypocotyl from observations 50, 60 and 70 days after sowing compared to other treatments.